Consequences of polyploidy and divergence as revealed by cytogenetic mapping of tandem repeats in African clawed frogs (Xenopus, Pipidae) - Fornaini, Nicola R; Bergelová, Barbora; Gvoždík, Václav; Černohorská, Halina; Krylov, Vladimír; Kubíčková, Svatava; Fokam, Eric B; Badjedjea, Gabriel; Evans, Ben J; Knytl, Martin (European journal of wildlife research, 2023)
Repetitive elements have been identified in several amphibian genomes using whole genome sequencing, but few studies have used cytogenetic mapping to visualize these elements in this vertebrate group. Here, we used fluorescence in situ hybridization and genomic data to map the U1 and U2 small nuclear RNAs and histone H3 in six species of African clawed frog (genus Xenopus), including, from subgenus Silurana, the diploid Xenopus tropicalis and its close allotetraploid relative X. calcaratus and, from subgenus Xenopus, the allotetraploid species X. pygmaeus, X. allofraseri, X. laevis, and X. muelleri. Results allowed us to qualitatively evaluate the relative roles of polyploidization and divergence in the evolution of repetitive elements because our focal species include allotetraploid species derived from two independent polyploidization events - one that is relatively young that gave rise to X. calcaratus and another that is older that gave rise to the other (older) allotetraploids. Our results demonstrated conserved loci number and position of signals in the species from subgenus Silurana; allotetraploid X. calcaratus has twice as many signals as diploid X. tropicalis. However, the content of repeats varied among the other allotetraploid species. We detected almost same number of signals in X. muelleri as in X. calcaratus and same number of signals in X. pygmaeus, X. allofraseri, X. laevis as in the diploid X. tropicalis. Overall, these results are consistent with the proposal that allopolyploidization duplicated these tandem repeats and that variation in their copy number was accumulated over time through reduction and expansion in a subset of the older allopolyploids.
Keywords: Amphibians; Anura; Allopolyploidization; snRNA; Histone H3; In situ hybridization